Measurement of the gamma ray background in the Davis cavern at the Sanford Underground Research Facility - Akerib, DS; Akerlof, CW; Alsum, SK; Boast, KE; Carels, C; Cottle, A; Fruth, T; Kraus, H; Liao, FT; Scovell, PR; Stevens, A (Elsevier, 2019)
Deep underground environments are ideal for low background searches due to the attenuation of cosmic rays by passage through the earth. However, they are affected by backgrounds from γ-rays emitted by 40K and the 238U and 232Th decay chains in the surrounding rock. The LUX-ZEPLIN (LZ) experiment will search for dark matter particle interactions with a liquid xenon TPC located within the Davis campus at the Sanford Underground Research Facility, Lead, South Dakota, at the 4850-foot level. In order to characterise the cavern background, in-situ γ-ray measurements were taken with a sodium iodide detector in various locations and with lead shielding. The integral count rates (0–3300 keV) varied from 596 Hz to 1355 Hz for unshielded measurements, corresponding to a total flux from the cavern walls of 1.9 ± 0.4 γ cm−2s−1. The resulting activity in the walls of the cavern can be characterised as 220 ± 60 Bq/kg of 40K, 29 ± 15 Bq/kg of 238U, and 13 ± 3 Bq/kg of 232Th.